2013
DOI: 10.1371/journal.pone.0063243
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts from Hepatocellular Carcinoma Promote Malignant Cell Proliferation by HGF Secretion

Abstract: Cancer-associated fibroblasts (CAFs) are reported to support tumorigenesis by stimulating angiogenesis, cancer cell proliferation, and invasion in most solid tumors. However, the roles of CAFs in the liver cancer microenvironment have not been thoroughly studied. In our previous study, we successfully isolated CAFs from hepatocellular carcinoma (HCC) (H-CAFs) and proved that H-CAFs suppressed the activation of NK cells and thereby created favorable conditions for HCC progression. In our present study, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 31 publications
3
94
1
Order By: Relevance
“…However, different types of growth factors and cytokines, such as SDF-1, HGF, epidermal growth factor (EGF), interleukin (IL)-6, and transforming growth factor (TGF)-β, implicated as autocrine and paracrine mediators of stromal-epithelial interactions are involved in tumor progression. 12,13,21,22 In this study, we observed that the CAFs secrete FGF-1 at a higher level than NFs. The function of FGF-1 was subsequently investigated in our study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, different types of growth factors and cytokines, such as SDF-1, HGF, epidermal growth factor (EGF), interleukin (IL)-6, and transforming growth factor (TGF)-β, implicated as autocrine and paracrine mediators of stromal-epithelial interactions are involved in tumor progression. 12,13,21,22 In this study, we observed that the CAFs secrete FGF-1 at a higher level than NFs. The function of FGF-1 was subsequently investigated in our study.…”
Section: Discussionmentioning
confidence: 50%
“…[10][11][12][13][14] FGF is one of the growth factors secreted by CAFs, which execute diverse functions by binding to and activating members of the fibroblast growth factor receptor 4 (FGFR4) family, such as cell survival, proliferation, and migration in a variety of cell types. 15,16 To date, 22 FGF genes have been identified in human, which are differentially expressed in many tissues.…”
Section: Introductionmentioning
confidence: 99%
“…HGF from CAFs regulates tumor growth, invasion, and proliferation of cancer cells in a variety of tumors[26][27][28][29].Exosomes are secreted microvesicles that are emerging as potent mediators of cell-cell communication. Luga et al revealed that CAFs-secreted exosomes promote breast cancer cell protrusive activity, motility, and metastasis via Wnt-planar cell polarity signaling[30].Some studies have demonstrated direct interactions between CAFs and cancer cells for proliferation, migration, cancer survival, and metastasis.…”
mentioning
confidence: 99%
“…Olumi et al found that CAFs could induce formation of tumors when simian virus 40-transformed prostate epithelial cells BPH-1 were coinjected with either CAFs or normal fibroblasts, indicating that CAFs can initiate tumorigenesis. [27][28][29] Similarly, neighboring CAFs could promote proliferation, migration and growth of oral cancer cells (OCCs) through enhancing the expression of cell cycle-driven proteins. 30 However, the involvement of CAFs in CRCs has not been well addressed.…”
Section: Discussionmentioning
confidence: 99%